Wajah Kristus dalam Malang sebagai Kota Urban. Refleksi Kristologis dalam Perspektif Urban - Makarius, Habel Melki (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2018)
As a historical civilized city which has developed towards an urban city. Malang is the focus of this article. The writer found out that Malang of today has shown its new face as an urbanized one which has offered a new kind of life values. He calls it the ‘face’ of an urban culture. He argues then that the new phenomena of Malang ought to be continuously imbued by the ‘spirit’ which has traditionally been well-known in the watchword of Malangkuçeçwara. From the Christian perspective, the spirit that has to be promoted is the Spirit of Christ, the ‘Urban’ as such. The society of urban Malang, particularly the Christian community is expected to let itself be animated by this ‘Spirit’ which is the source of the dynamic of urban life. The writer concludes that the urbanized city of Malang for the Christians is the very locus of pursuit and encounter with Christ, the Urban.